Comprehensive Review of Laboratory Role in Disease Diagnosis and Health Monitoring - SAYYAR, ALRESHIDI MOUSA; ALZUBUN, FAHAD SALEEM MUFLH; ABDULRAHMAN S, ALSUWAYDAA, YOUSEF; ALRASHDI, NASSER SHURAYWID OSYWOOD; ALGHASLAN, FAHAD YAHYA FAHAD; ALRESHIDI, BUNDER ABDUIIAH TUIQ; ABDULRAHMAN E, ALRASHDI, AHMED; DAKHEEL M, ALRESHIDI AHMED; AlRashidi, MABRUK BADI M; ALI K, ALAZMI, AHLAM (Journal of Ecohumanism, 2024)
The Sputnik of the diagnostic, analytical, and managerial work in the branch of laboratory medicine is critical in the current world. Due to the advancement of technologies in the laboratory and diagnostic instruments, laboratory professionals play an important role in healthcare planning for doctors to improve patients' care. This comprehensive review looks at the laboratory in the context of disease diagnosis and health surveillance, particularly regarding early detection, disease surveillance, and control. It also discusses new opinions, trends, laboratory personnel diagnostic problems, and laboratory data used in clinical decisions. The following review can be based on the recovery of literature published within the last 5–10 years to establish the essential role of laboratories in modern healthcare.